NONALCOHOLIC FATTY LIVER DISEASE IN SEVERE OBESE PATIENTS, SUBJECTED TO BARIATRIC SURGERY - LOSEKANN,Alexandre (2013)
ContextNonalcoholic fatty liver disease encompasses a spectrum of histopathological changes that range from simple steatosis to nonalcoholic steatohepatitis. Works suggest that iron (Fe) deposits in the liver are involved in the physiopathology of nonalcoholic steatohepatitis.ObjectiveThe aim of this study was to determine the prevalence of simple steatosis and nonalcoholic steatohepatitis in patients with morbid obesity, subjected to bariatric surgery and to establish a correlation of the anatomopathological findings with the presence of liver fibrosis.MethodsA total of 250 liver biopsies were conducted in the transoperation of the surgeries.ResultsSteatosis was present in 226 (90.4%) of the samples, 76 (30.4%) being classified as mild; 71 (28.4%) as moderate and 79 (31.6%) as intense. Nonalcoholic steatohepatitis was diagnosed in 176 (70.4%) cases, where 120 (48.4%) were mild; 50 (20%) were moderate, and 6 (2.4%) cases were intense. Fibrosis was referred to in 108 (43.2%) biopsies, 95 of which (38%) were mild; 2 (0.8%) were moderate; 7 (2.8%) were intense, and cirrhosis was diagnosed in 4 (1.6%) cases. There was a correlation between the degree of steatosis and the level of inflammatory activity (rs = 0.460;P<0.001) and between the degree of this activity and the degree of fibrosis (rs = 0.583;P<0.001). Only 13 (5.2%) samples showed Fe deposits.ConclusionThere is a high prevalence of nonalcoholic steatohepatitis in these patients and a positive correlation of the degrees of nonalcoholic steatohepatitis with the intensity of fibrosis. The low prevalence of Fe deposits found makes it questionable that the presence of this ion has any participation in the physiopathogeny of nonalcoholic fatty liver disease.